Production Potential of Guinea Grass Clones Under Partial Shade in Coconut Gardens - Thejasee Bhai V (Department of Plant Breeding, College of Agriculture, 1988)
A research programme was carried out at the Department of Plant Breding, College of Agriculture, Vellayani, during June to December, 1987 with the objective of evaluating the expression of production potential of guinea grass clones under partially shaded conditions in coconut plantations through estimation of genetic variability, correlation of green fodder yield and other components and the direct and indirect effects of different components on green fodder yield. Fifteen varieties of guinea grass were evaluated under partially shaded condition in the inter spaces of coconut plantation, adopting a randomized block design replicated thrice. Data on thirteen characters were recorded and subjected to analysis of variance and covariance. The genotype and phenotypic coefficient of variation, heritability in the broad sense, genetic advance and genotype and phenotypic correlations were estimated. Path analysis was conducted using green fodder yield per plot as the effect and five component characters as the cause. Analysis of variance revealed significant differences among the varieties for plant height, number of tillers per hill, number of panicles per plot, leaf: stem ratio on fresh weight and dry weight bases, green fodder yield per hill and per plot, dry matter yield per hill and Leaf Area Index. Analysis of variance for chlorophyll pigment contents (chlorophyll ‘a’, ‘b’ and total pigments) and dry matter yield per plot revealed that there was no significant difference among the varieties. High genotypic coefficients of variation, moderate to high heritability and genetic gain were recorded for the yield components viz., green fodder yield per hill, leaf: stem ratio and Leaf Area Index suggesting the reliability of these characters during selection programmes for the improvement of this crop. Green fodder yield per plot recorded high positive genotypic correlation with tiller number per hill, green fodder yield per hill, dry matter yield, leaf: stem ratio and Leaf Area Index. Path analysis revealed that green fodder yield per hill had the maximum direct contribution for green fodder yield per plot, followed by leaf: stem ratio on fresh weight basis, number of tillers per hill and plant height. Leaf Area Index exhibited negative direct effect and positive indirect effect through green fodder yield per hill and leaf: stem ratio on fresh weight basis on green fodder yield per plot. It can be suggested that an ideal plant type of guinea grass for cultivation under partially shaded conditions should have high Leaf Area Index more number of leaves resulting in high green fodder yield per hill. Thus green fodder yield per hill, leaf: stem ratio on fresh weight basis and Leaf Area Index may be considered in breeding programmes for developing high fodder yielding guinea grass varieties suited to partially shaded conditions of coconut plantations.